1867 N.H. Gen. Stat. 206 - (:unkn) unknown (My University, 1854)
Ch. 98, §§ 1-4: Provided the board of firewards the ability to regulate the import/export of Gunpowder. Also prohibited the storage of gunpowder in quantities exceeding 25 pounds
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER